Papel do processo oxidativo/inflamatório na fisiopatologia induzida por concussões recorrentes em ratos jovens - Cipolat, Rafael Parcianello (2022)
Concussion can be defined as a change in brain function caused by an external force. In recent years, it has received greater attention from the scientific community for its subtle effects, which can add up and worsen the secondary damage of the injury. It’s very common in the context of sports initiation in schools, recurrent concussions (RC) lack studies that evaluate their long-term effects on the central nervous system (CNS). Interest is growing about the effects of CR in adolescence can influence neural architecture and metabolism in adulthood, in different situations and pathologies. Thus, to investigate this knowledge gap, the present work submitted 35-day-old rats to a protocol of 7 CR (one per day). The analysis of the behavioral tests applied 30 days after the last CR revealed that there was a decrease in short- and long-term memory in the object recognition test and, in addition, there was no change in motor and anxious behavior. In addition, the CR protocol induced 34 days after the last insult the inflammatory/oxidative stress characterized by the increase of glial fibrillary acidic protein (GFAP), interleukin-1β (IL-1β), 4-hydroxynonenal (4-HNE), immunoreactivity of protein carbonyl and oxidation of 2',7'-dichlorofluorescein diacetate (DCFH) and lower total antioxidant capacity (TAC). In addition, through statistical analysis it was also revealed that CR alter the activity and expression of the enzyme Na+, K+-ATPase, specifically, the inhibited Na+,K+-ATPase activity (α2/3 isoform) and decreased immunodetection of the alpha subunit of this enzyme. With these results, it is plausible to propose that cognitive impairment after CR is caused by the inability of neurons to survive because they cannot maintain ionic gradients in selected targets for inflammatory/oxidative damage, such as Na,K-ATPase enzyme activity.